Influence of technological parameters on the mechanical properties of NT-50 superconducting multistrand conductors at low temperatures - Lototskaya, V.A.; Il'ichev, V.Ya.; Buryak, V.P.; Matrosov, N.I. (Проблемы прочности, 1985)
The purpose of this article is to study the influence of thermomechanical working, strand diameter, and space factor on the mechanical characteristics of NT-50 alloy-base superconducting multistrand conductors in the 4.2-300°K range.